Variasi Media Dalam Mengajarkan Calistung Di Raudlatul Athfal Babul Jannah Sambas - Purnama, Sigit; Multahada, Asyruni (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2016)
Calistung (reading, writing and numeracy) learning in early childhood controversy among the public because it is considered a bad impact on child's mental. RA Babul Jannah Sambas is one of the early childhood institutions that implement Calistung learning in early childhood by applying a variety of media learning. This study aims to describe empirically the use of variations of instructional media in teaching Calistung in RA Babul Jannah Sambas. This research use qualitative approach with data collecting technique through interview, observation and documentation. The results of this study concluded that: 1) the media is varied, i.e. human, APE, and programs/activities. Techniques variety of media consisting of: a) vary some of the learning media in all meetings, b) varying one media with several learning methods, c) use different media every day, d) using the media in the time index, and e) varying the use of media outside the classroom. Whereas, the activities of the variety of media in the learning process consists of planning, preparation, implementation and evaluation; 2) the use of a variety of instructional media in teaching Calistung have a considerable impact both on the development of early childhood; 3) the advantages of the use of a variety of media including sparking the interest and attention of the child, train the skills Calistung, and minimize the flavor saturated and bored. While, the drawback is the need to provide different media every day, while the number of media available is very limited. The efforts of teachers in overcoming the shortcomings, such as the teacher using the division of the group and turn in a media play.